Kapasitas Antioksidan dan Sifat Fisikokimia Hidrolisat Kolagen dari Kulit Ikan Tuna Sirip Kuning dengan Metode Ultrasound Assisted Enzymatic Reaction: The Antioxidant Capacity and Physicochemical Properties of Yellowfin Tuna Skin Collagen Hydrolysate Using Ultrasound-Assisted Enzymatic Hydrolysis - Raden Hilman Wirayudha; Dian Herawati; Feri Kusnandar; Tati Nurhayati (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Pepsin soluble collagen hydrolysate from yellowfin tuna skin is a derivative product obtained from the hydrolysis of pepsin soluble collagen using a combination of enzymatic extraction process with protease enzymes (Alcalase®) and physical extraction using ultrasonication method. Collagen hydrolysate has many advantages, especially in its wide use and better physicochemical characteristics and functional properties compared to collagen. The aims of this study were to produce collagen pepsin from yellowfin tuna skin, to evaluate the effect of sonication time and concentration of alcalase enzyme to obtain the optimum hydrolysate product, to compare the physicochemical characteristics and antioxidant capacity of pepsin soluble collagen and its hydrolysate. The pepsin soluble collagen was obtained by acid extraction using acetic acid and pepsin enzyme with a concentration of 750 U/mg. Data analysis to determine optimum hydrolysis conditions using a factorial completely randomized design with two factors. The optimum collagen hydrolysate with the highest degree of hydrolysis, as well as antioxidant inhibition of the DPPH and ABTS methods, was obtained with the addition of 2:20 Alcalase® enzyme (enzyme/mg protein) treatment with a hydrolysis time of 2 hours using the ultrasonication method. The hydrolysis process of collagen into its hydrolysate can improve its physicochemical characteristics and antioxidant capacity, including a lower molecular weight of up to 5 kDa, increased total amino acids up to 56.93%, increased water solubility up to 99.54%, and higher antioxidant capacity inhibition on DPPH method with IC50 of 77.2 mg/L and ABTS method with IC50 of 40.72 mg/L.